A Legal Review of Corporate Governance Implementation in Developing Countries: A Bibliometric Analysis of Regulatory and Policy Developments - Judijanto, Loso; Purwoto, Ady; Lubis, Arief Fahmi (West Science Law and Human Rights, 2025)
Corporate governance plays a pivotal role in fostering transparency, accountability, and sustainable economic development, particularly in developing countries. This study conducts a bibliometric analysis using data from Scopus and VOSviewer to explore the academic discourse on corporate governance with a focus on regulatory and policy developments. The analysis reveals "corporate governance" as the central theme, with strong connections to "developing countries," "corporate social responsibility," and "firm performance." Key findings highlight the significance of regulatory frameworks, transparency, and board structures in enhancing governance practices, while also emphasizing the growing integration of corporate governance with strategic dimensions such as market performance and corporate strategy. Despite these advancements, gaps in the literature remain, particularly concerning the role of informal institutions, cultural influences, and technological innovations in governance. This study underscores the need for tailored governance frameworks that address the unique challenges of developing countries while aligning with global best practices. These insights provide valuable directions for policymakers, practitioners, and scholars aiming to enhance corporate governance in emerging economies.